Enhancing the Handover Performance in the Mobile Heterogeneous Network Based on the Expected Zone of Handover Events (University of Khartoum Engineering Journal, 2022)
This paper aims to enhance the handover performance in the heterogeneous networks (HetNet)by reducing the need to make handover under the specified conditions and also reducing the handover failure, thisstudy divided the target cell for ten assumed circular zones, where zones start with radius Rh=R/10 from center of target cell, then the next zone is increased by R/10, then the simulation is carried out for each assumed zone usingselective values of TTT (160,480 and 640 ms) in order to determine the best circular zone of more handover events (zone of handover) in the coverage area for the target cell and other zone for no handover events (zone of no handover).The paper found that the most practically suitable zone for more handover events was the zone which its radius represents 86.6% of the radius of the coverage area for the target cell. Whereas, the remained zone (the zone between the zone of handover and the edge of target cell is considered a zone for no handover events. Also, the angle of chord (Ѳ) for the expected zone of handover events from the horizontal axis is 60˚, i.e. if the UE moves bycertain velocity and with a moving angle less than or equal to 60˚, then it will have a large probability to make handover events after satisfying the other handover conditions. Otherwise, its probability to make handover events is very low. The paper extracted that after determining more suitable handover zone and implementing the different fixed and chosen values of TTT, then a remarkable enhancement occurred in the handover performance and it was obvious at high speed of travelling for the user.